Immunogenicity of Modern Vaccine Viruses of Influenza A (H1N1)pdm09 According to Graphical Analysis - V. S. Vakin; O. S. Konshina; E. M. Wojciechowska; E. V. Kuznetsova; V. G. Mayorova; A. A. Vasilyeva; I. Yu. Nikonorov (Эпидемиология и вакцинопрофилактика, 2017)
Antiepidemic measures were limited effectiveness for several years Objectives of this research were formulated as an assessment of the immunogenicity activity of the influenza virus A(H1N1)pdm09 in the composition of modern trivaccines Immunogenicity of the influenza virus A(H1N1)pdm09 in the vaccinated by vaccine was assessed by graphing, reflecting the dynamics of the multiplicity growth of antibodies (MG) and medium ratio of antibodies increasing (MR) in sera for several groups vaccinated. For comparison of vaccinated immunity was determined by traditional methods of evaluation of the immune response. As a result of the research, differences in the immunogenicity activity of the virus were revealed, which are reflected in antibody titers and the multiplicities of their growth from 2 to 4 - 8 times with the applying of similar quality vaccines. These changes couldn’t be observed with accounting study of the immune response. When immunized with a vaccine with an antigen dose of 5 mg HA identified a group of«silent» volunteers (8%) who did not respond to promotion with antigen A(H1N1)pdm09. Increasing dose of the influenza virus A(H1N1)pdm09 to 15 mg/dose in the split vaccine were result of the elimination of the group of«silent» volunteers. Simultaneously was observed a significant increase in the immune response in serum titers (up to 32-fold) and antibody growth rates Accordingly, using of the graphical form of accounting made it possible to better assess the details of the formation of collective immunity to the virus A(H1N1)pdm09 and the nature of its deviations in a number of cases.